2017
DOI: 10.4094/chnr.2017.23.1.28
|View full text |Cite
|
Sign up to set email alerts
|

Family-Centered Care for Hospitalized Children: Concept Analysis

Abstract: Purpose: Involvement of families in rounds is one strategy to implement patient-and family-centered care to help families get clear information about their child, and be actively involved in decision making. The purpose of this paper was to identify the major concepts of family-centered rounds for hospitalized children. Methods: We searched five electronic databases for relevant articles and used Whittemore and Knafl' s integrative review methods to synthesize the literature. Articles published between June 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 38 publications
1
9
0
2
Order By: Relevance
“…While an increasing amount of research has focused on family-centered care in Korea, for the most part this research has consisted of conceptual analyses and the development of instruments related to family-centered care [4,[12][13][14]. It is not enough to elicit implications, because these efforts have not yielded results that can be applied directly to the clinical field.…”
Section: Introductionmentioning
confidence: 99%
“…While an increasing amount of research has focused on family-centered care in Korea, for the most part this research has consisted of conceptual analyses and the development of instruments related to family-centered care [4,[12][13][14]. It is not enough to elicit implications, because these efforts have not yielded results that can be applied directly to the clinical field.…”
Section: Introductionmentioning
confidence: 99%
“…Family-centered care (FCC) is respectful and inclusive of the patient's family in healthcare decision-making and can be applied in clinical settings regardless of the patient's age or severity of illness [1]. FCC emphasizes the mutually beneficial partnership between healthcare providers, including nurses, and the patient and his or her family, and its main concepts are respecting and honoring families, sharing information, encouraging participation and cooperation, and supporting families [1][2][3]. Extensive research has reported that FCC brings positive results to patients and their families and increases their satisfaction level, while also decreasing medical expenses, which contributes to the effective utilization of medical resources [4].…”
Section: Introductionmentioning
confidence: 99%
“…In other countries, applied intervention studies of FCC on a wide range of subjects, not restricted to children, are being actively conducted [14]. Korean scholars have recently started to pay attention to FCC and have conducted descriptive studies, such as a concept analysis on hospitalized children's FCC [3], a concept analysis on parent participation in the care of hospitalized children [8], and an integrative review of family-centered rounds in care for hospitalized children [10].…”
Section: Introductionmentioning
confidence: 99%
“…The philosophical basis of child health nursing care lies in FCC, which considers both children and their families as targets for nursing care [ 41 , 42 ]. Family-centeredness is an important concept not only in nursing but also in medicine [ 36 ].…”
Section: Discussionmentioning
confidence: 99%